Diseño de un sistema automatizado con energía fotovoltaica para riego en cultivo de cítricos (2022)
This work raised the design of an automated system with photovoltaic energy for irrigation in citrus cultivation, with this, it was intended to obtain the maximum use of water resources for agricultural purposes, seeing drastic changes in production, greater yield, and quality of products, putting into practice concepts learned during the period of academic training as a Technologist in Mtto. Electromechanical. Being essential the design of an automated irrigation system with photovoltaic energy, where each of the elements that make it up could be studied.